En embuscade sur le sentier de l’argent. Une perspective internationale - Levi, Michael (Criminologie, 1997)
This article examines the growth of financial measures against 'organised crime' in the form of money-laundering and asset confiscation. After discussing the implications of conflicts over what crimes should be included in money-laundering statutes —e.g. drugs-only or all 'serious' crime —it summarises the findings of a research study conducted by the author into the impact of money-laundering reporting in the UK upon criminal investigation by the police and customs, and into the forfeiture of the proceeds of crime. It concludes that these measures have had a very limited effect and will continue to do so, unless more technological and human resources are put into the investigation process. Furthermore, the tendency of offenders at all but the highest levels to spend their money as they go along places limits on the likely impact of these measures, based as they are on a model of criminal organisation that is more than the reality.